2006
DOI: 10.1097/01.rti.0000209820.35755.e9
|View full text |Cite
|
Sign up to set email alerts
|

Venous Hemangioma Arising From the Diaphragm

Abstract: We report a rare case of diaphragmatic hemangioma with computed tomography and magnetic resonance imaging findings. A routine chest radiograph in a 75-year-old woman revealed a nodular opacity in the right lower lung field. Multidetector-row computed tomography revealed a well-circumscribed nodule arising from the diaphragm or pleura. Dynamic magnetic resonance imaging of the nodule showed a pattern of gradually increasing signal intensity. On the basis of the intraoperative and histopathologic findings, venou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It is common to diagnose hepatic hemangioma by abdominal dynamic three-phase CT. Kono et al[5] reported a case of diaphragmatic hemangioma using dynamic imaging findings. On contrast-enhanced dynamic MRI images of T1-weighted imaging, the lesion showed a gradual enhancement pattern, which was maintained in the late phase.…”
Section: Discussionmentioning
confidence: 99%
“…It is common to diagnose hepatic hemangioma by abdominal dynamic three-phase CT. Kono et al[5] reported a case of diaphragmatic hemangioma using dynamic imaging findings. On contrast-enhanced dynamic MRI images of T1-weighted imaging, the lesion showed a gradual enhancement pattern, which was maintained in the late phase.…”
Section: Discussionmentioning
confidence: 99%